ORIGINAL ARTICLE The problem of eosinophilia in chronic urticaria - Marciniak, Adriana; Wegener, Joanna; Jenerowicz, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
The main purpose of the present study was to analyze peripheral blood eosinophilia phenomenon in patients suffering from chronic urticaria with regard to particular elements of patients’ examination as well as severity of the disease. 60 chronic urticaria patients were investigated. The age of patients ranged from 5-70 years. There were 81.7% female patients and 18.3% male patients in the analyzed group. We evaluated the number of wheals, maximum diameter of the largest wheal and severity of pruritus. Furthermore, measurements of peripheral eosinophilia using Carpentier’s method and differential white-blood-cell count were performed. Among 60 chronic urticaria patients, 3 subjects (5%) presented increased value of peripheral blood eosinophilia using Carpentier’s method. High percentage of eosinophils in the differential white-blood-cell count (>4 %) was observed in 8 individuals (13.3 %). There was no statistically significant difference between chronic urticaria patients and healthy subjects considering mean level of peripheral blood eosinophilia assessed using both described methods. Additional statistical analysis using ROC curves confirmed, that measurements of peripheral blood eosinophilia could not serve as a useful parameter discriminating healthy individuals from chronic urticaria patients. Moreover, the value of peripheral blood eosinophila in patients suffering from fairly severe/severe urticaria was lower than in patients with mild/moderate disease, suggesting that destruction of eosinophils, life shortage or increased migration to the tissues might have taken place. Additionally, a statistically significant correlation between peripheral blood eosinophilia analyzed using two described methods could be observed (p<0.001). Present study suggests, that low level of peripheral blood eosinophilia is a significant feature of chronic urticaria. Therefore, in case of severe chronic urticaria with concomitant high number of peripheral blood eosinophils various etiopathogenetic factors should be taken into consideration (proliferative and autoimmunological diseases, hormonal disturbances as well as parasitoses and atopic diseases).